By-Product Synergy from Nipa Palm Frond Processing Waste Ban Laem Community, Trang Province - Piyang, Tuanjai; Khuawaraphan, Rarin (Area Based Development Research Journal, 2019)
Most people in Palian river basin of Ban Laem community, Kantrang district, Trang province have utilized the local resources of Nipa palm to produce cigarette paper and earned side income. The palm peeling process leaves the waste of the Nipa palm frond and shaft, resulting in disposal problems. Thus, the purpose of this study is to increase the value of the left-behind material from Nipa palm frond by making two new products, namely plant pots and fancy charcoal deodorizer.The research process involves both laboratory work and participatory action research by the community. The steps are as follows: 1) Analysis, synthesis of community data 2) Products development from by-product Nipa palm frond 3) Transferring knowledge and technology to the community. 4) Ban Laem community cluster, and 5) Marketing promotion. The results indicate Ban Laem community’s initial problems of Nipa palm frond waste, especially on visual environment of the communities’ landscapes. The study exploits the Nipa palm frond by-product as material for plant pot production. The experiment has determined the three materials as by-product of Nipa palm frond: soil : pastry glue, at the ratio of 4.0 : 1.0 : 4.0, which is the best optimal mixing ratio for molding. For the production of fancy charcoal deodorizer Nipa palm frond, the experiment sets the ratio of activated charcoal : pastry glue as 0.9:10, which is the best optimal value for molding step, smooth surface, durability, and appropriate humidity, corresponding to standard mark on the community product, licensed for charcoal odour absorber (SCP No. 180/2546). The knowledge and technology transfer to Ban Laem community results in community clustering and founding an enterprise called Palian Community Enterprise Group. The members collaborate to promote the products and extend distribution channels in various forms, such as co-organizing exhibitions with public and private sectors, and publicizing on fan page Facebook channel to raise public interest. The project helps increase the community’s revenues and improve the quality of life.